2020
DOI: 10.1002/slct.202000523
|View full text |Cite
|
Sign up to set email alerts
|

B, N‐codoped Cu–N/B–C Composite as an Efficient Electrocatalyst for Oxygen‐Reduction Reaction in Alkaline Media

Abstract: As an alternative for platinum‐based electrocatalysts, the development of non‐precious metal catalysts for oxygen reduction reaction (ORR) is highly desirable for fuel cell applications. In this paper, we propose a facile preparation method for a B, N‐codoped Cu–N/B–C nanomaterial as an efficient electrocatalyst for ORR in alkaline electrolytes. One‐step heat treatment of cyanamide/melamine, boric acid, and cupric chloride loaded on carbon black produces a Cu–N/B–C composite with a high specific surface area. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…High-resolution N 1s XPS spectra of as-synthesized catalysts could be fitted into five peaks, which belonged to pyridinic N (398.0 eV), Fe–N (399.2 eV), pyrrolic N (400.1 eV), graphitic N (400.8 eV), and oxidized N (402.1 eV) (Figure b). Notably, pyridine nitrogen, Fe–N x , and graphite nitrogen accounted for the largest proportion of Fe–B–N–C. Previous studies have shown that pyridine nitrogen and graphite nitrogen have a decisive effect on the formation of Fe–N x and promoted the four-electron process of ORR. , As shown in Figure c, high-resolution B 1s XPS spectra showed the three valence states of B, involving B–N–C (189.2 eV), BC 3 (190.7 eV), and B–O (191.6 eV) in Fe, B, N codoped, and B, N codoped samples. , Among them, the 3-fold-coordinated BC 3 phase can promote the ORR performance due to its strong electron-donor ability . In addition, the interaction between adjacent B and N atoms could promote the charge transfer of adjacent carbon atoms, facilitate the adsorption of O 2 , and weaken the OO bond. ,, The high-resolution Fe 2p XPS spectra of Fe–B–N–C and Fe–N–C (Figure d) showed the existence of Fe 3+ (712.5 and 725.3 eV) and Fe 2+ (710.2 and 723.3 eV) peaks .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…High-resolution N 1s XPS spectra of as-synthesized catalysts could be fitted into five peaks, which belonged to pyridinic N (398.0 eV), Fe–N (399.2 eV), pyrrolic N (400.1 eV), graphitic N (400.8 eV), and oxidized N (402.1 eV) (Figure b). Notably, pyridine nitrogen, Fe–N x , and graphite nitrogen accounted for the largest proportion of Fe–B–N–C. Previous studies have shown that pyridine nitrogen and graphite nitrogen have a decisive effect on the formation of Fe–N x and promoted the four-electron process of ORR. , As shown in Figure c, high-resolution B 1s XPS spectra showed the three valence states of B, involving B–N–C (189.2 eV), BC 3 (190.7 eV), and B–O (191.6 eV) in Fe, B, N codoped, and B, N codoped samples. , Among them, the 3-fold-coordinated BC 3 phase can promote the ORR performance due to its strong electron-donor ability . In addition, the interaction between adjacent B and N atoms could promote the charge transfer of adjacent carbon atoms, facilitate the adsorption of O 2 , and weaken the OO bond. ,, The high-resolution Fe 2p XPS spectra of Fe–B–N–C and Fe–N–C (Figure d) showed the existence of Fe 3+ (712.5 and 725.3 eV) and Fe 2+ (710.2 and 723.3 eV) peaks .…”
Section: Resultsmentioning
confidence: 88%
“…The chemical state of various atoms was investigated by X-ray photoelectron spectroscopy (XPS). As shown in Figure S4, the XPS survey spectrum of Fe−B−N−C catalysts showed the presence of Fe 55,56 Among them, the 3-fold-coordinated BC 3 phase can promote the ORR performance due to its strong electron-donor ability. 57 In addition, the interaction between adjacent B and N atoms could promote the charge transfer of adjacent carbon atoms, facilitate the adsorption of O 2 , and weaken the OO bond.…”
Section: Resultsmentioning
confidence: 99%
“…While iron, cobalt and manganese are the most utilised transition metals to prepare SACs for the AEMFC cathode as was evident from prior, then in recent years good performance in single-cell AEMFC tests has also been obtained with other cheap and widely available metals, such as zinc and copper (see Table 2). [182,[184][185][186] Zinc has been mostly used in the preparation of FeÀ NÀ C single-atom electrocatalysts, whether to modify the porous structure with ZnCl 2 or using ZIF-based MOFs, and then removing the zinc as unwanted weight as it is mostly shown to be rather inactive towards the ORR. However, recently Sun et al [182] showed both theoretically via DFT calculations and experimentally that atomically dispersed Zn-sites could indeed be ORR-active if Zn is combined with pyrrolic-N moieties.…”
Section: Cathode Electrocatalyst Based On Other Atomically Dispersed ...mentioning
confidence: 99%
“…20 A B,N-codoped Cu-N/B-C nanomaterial was prepared as an ORR catalyst in alkaline electrolytes, which demonstrated superior stability and higher tolerance to methanol crossover in comparison to Pt/C catalyst, and was also shown to have suitable properties for use in an AEMFC. 58 Microstructure and the fabricating method of electrodes associated with their transport resistances and electrochemical kinetics are critical for the improvement of cell performance. Modern AEMFC electrocatalyst layers are usually composite structures of anion conducting ionomer material and noble or non-noble metal catalyst, usually supported on carbon.…”
Section: Oxygen Reduction Reaction (Orr) At Cathodementioning
confidence: 99%